Health Literacy and Adherence to Clinical Recommendations in Head and Neck Cancer - Randall J. Harley; Karley Atchison; Jinhong Li; Karen Losego; Tamara Wasserman-Wincko; Jonas T. Johnson; Marci L. Nilsen (SLACK Incorporated, 2023)
Background: After definitive cancer treatment, survivors of head and neck cancer (HNC) are commonly recommended to participate in therapies aimed at reducing the burden of treatment-related side effects. Objective: In this study, we evaluated whether adherence to referral to physical therapy (PT) and speech-language pathology therapy (SLPT) is related to patient health literacy (HL). Methods: This is a retrospective cohort analysis of patients attending a multidisciplinary HNC survivorship clinic between 2017 and 2019. HL was measured using the Brief Health Literacy Screen, with scores below 10 indicating inadequate HL. Chi-square and logistic regression were used to evaluate the association between HL and adherence to PT or SLPT referral. Key Results: From the overall cohort (N = 454), 80 patients (18%) had inadequate HL. Compared to those with adequate HL, patients with inadequate HL were significantly less likely to complete initial PT evaluation (74% vs. 58%, p = .034) but were not significantly less likely to complete initial SLPT evaluation (70% vs. 61%, p = .37). After adjusting for age, primary tumor site, and treatment stage, we found that patients with inadequate HL were half as likely to follow up for initial PT evaluation (odds ratio 0.45, p = .032). Conclusion: Overall, inadequate HL is associated with reduced adherence to PT but is not associated with adherence to SLPT among HNC survivors. These results highlight the clinical importance of HL and underscore the need for interventions to facilitate adherence to treatment for patients with inadequate HL. [HLRP: Health Literacy Research and Practice. 2023;7(1):e52-e60.]